Zur Wirkung von Grünen Nudges im Gewässerschutz: Eine experimentelle Untersuchung mithilfe eines Unternehmensplanspiels; The Effects of Green Nudges in Water Protection - An Experimental Investigation using a Business Management Game - Denise Peth; Oliver Mußhoff; Katja Funke; Norbert Hirschauer (German Journal of Agricultural Economics (GJAE), 2018)
Stickstoffeinträge in Oberflächengewässer stellen ein schwerwiegendes Externalitätenproblem der landwirtschaftlichen Produktion dar. Umwelt- und Verbraucherschützer fordern, diese Externalitäten durch staatliche Eingriffe zu reduzieren. Vor diesem Hintergrund betrachtet die vorliegende Studie verhaltensbasierte Regulierungsstrategien in Form von Grünen Nudges. Anhand eines mehrperiodischen Einpersonen-Unternehmensplanspiels mit Studierenden der Agrarwissenschaften wird untersucht, wie Nudges auf die Einhaltung von Mindestabständen zu Gewässern bei der Düngung wirken. Untersucht werden ein Nudge mit Informationen und Bildern, die umwelt- und gesundheitsschädliche Auswirkungen bei Nichteinhaltung des Mindestabstands zeigen, sowie ein Nudge mit Informationen, Bildern und sozialem Vergleich, der einen Hinweis auf die Regelbefolgung durch die Mehrheit der Landwirte aus derselben Region beinhaltet. Es ergeben sich drei zentrale experimentelle Befunde: Erstens, die Nudges wirken im Experiment präventiv und verringern sowohl den prozentualen Anteil regelverstoßender Teilnehmer als auch den Gesamtumfang der regelwidrig gedüngten Fläche. Zweitens wirkt das Nudge mit Informationen, Bildern und sozialem Vergleich weniger stark präventiv als das einfache Nudge mit Informationen und Bildern. Drittens, innerhalb der regelbrechenden Teilgruppe steigt die regelwidrig gedüngte Fläche durch die Nudges, und zwar durch das Nudge mit sozialem Vergleich etwas stärker als ohne. Das Ergebnis ist damit (trotz der eingeschränkten Generalisierbarkeit eines Experiments mit Studierenden), dass sich die Wirkung von Nudges in verschiedenen Teilgruppen unterscheidet. In einer Teilgruppe wirkten die Nudges als Prävention. Innerhalb der regelbrechenden Teilgruppe erhöhten die Nudges aber die Schwere der Verstöße. Über die Gründe hierfür (z. B. Reaktanz) muss zum gegenwärtigen Zeitpunkt spekuliert werden. Die potenziell entgegengesetzte Wirkung ein und derselben Politikmaßnahme erscheint aber ein wichtiger Gegenstand zukünftiger Forschung (Politikfolgenabschätzung) zu sein (Quelle: Verlag). –SW: Unternehmensplanspiele; Verhaltensökonomik; Nudge; Ex-Ante-Politikfolgenabschätzung;Nitrogen runoffs induced by agricultural fertilization cause serious environmental damage to surface waters. Environmental and consumer protectionists demand government intervention to mitigate these externalities. With this in mind, the present study examines the effects of nudge-based regulatory strategies. We use an incentivized multi-period single-player business management game as experimental device to study how nudges affect compliance with the minimum-distance-to-water rule in a sample of agricultural science students. We analyse two different nudge treatments: a nudge with pictures showing environmental and health damages that are presumably caused by breaching the minimum-distance-to-water rule, and a nudge with an additional social comparison, which suggests that the majority of farmers in the same region comply with the rule. We observe three core experimental outcomes: first, nudging has a preventive effect and reduces not only the share of non-compliant participants but also the total acreage that is irregularly fertilised. Second, against all expectations, the preventive effect of the nudge with pictures and a social comparison is weaker than that of the nudge with pictures alone. A further contra-intuitive result is that nudging increases the severity of infringements (in terms of the irregularly fertilised acreages) among the nonetheless remaining offenders; and this effect is even a bit stronger for the nudge with additional social comparison. Despite the overall limited generalizability of experimental findings based on student participants, the results show that nudging produced very different behavioural effects in different groups: It worked well as a preventive device in one subgroup, but within the rule-breaking group it increased the severity of offences. At present, we can only speculate about the drivers behind these contrary effects (e.g., reactance). However, the indication that the same policy measures might work in opposite directions in different subgroups provides an important subject of future research (policy impact analysis). –SW: business management games; behavioural economics;nudge; ex-ante policy impact analysis – – Nitrogen runoffs induced by agricultural fertilization cause serious environmental damage to surface waters. Environmental and consumer protectionists demand government intervention to mitigate these externalities. With this in mind, the present study examines the effects of nudge-based regulatory strategies. We use an incentivized multi-period single-player business management game as experimental device to study how nudges affect compliance with the minimum-distance-to-water rule in a sample of agricultural science students. We analyse two different nudge treatments: a nudge with pictures showing environmental and health damages that are presumably caused by breaching the minimum-distance-to-water rule, and a nudge with an additional social comparison, which suggests that the majority of farmers in the same region comply with the rule. We observe three core experimental outcomes: first, nudging has a preventive effect and reduces not only the share of non-compliant participants but also the total acreage that is irregularly fertilised. Second, against all expectations, the preventive effect of the nudge with pictures and a social comparison is weaker than that of the nudge with pictures alone. A further contra-intuitive result is that nudging increases the severity of infringements (in terms of the irregularly fertilised acreages) among the nonetheless remaining offenders; and this effect is even a bit stronger for the nudge with additional social comparison. Despite the overall limited generalizability of experimental findings based on student participants, the results show that nudging produced very different behavioural effects in different groups: It worked well as a preventive device in one subgroup, but within the rule-breaking group it increased the severity of offences. At present, we can only speculate about the drivers behind these contrary effects (e.g., reactance). However, the indication that the same policy measures might work in opposite directions in different subgroups provides an important subject of future research (policy impact analysis).
Keywords: 330